Creative processes in laboratory: the production of intimacy in the disruptive territory of virtual gatherings (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Biographical/autofictional processes teach us to face the devices of biopolitical control over our immaterial production, especially the affections. These narratives of intimacy are a radiant invitation for the subject´s radical reinvention, for the remake of the affection map and the confrontation of intimidating “realities”. Can this promise of intervention and emancipation pointed out with narratives of intimacy still work in a virtual territory? Can the decolonization, demercantilization, and deprivatization of bodies be performed in a remote artistic practice? Where is the interaction between bodies impossible? How to produce bipotent bodies in the disruptive territory of virtual gatherings? This is the reflection proposed by this article.
Keywords: Autofiction; Biopotency; Decolonization